Proprioception - Vega, José A.; Cobo, Juan (IntechOpen, 2021)
Proprioception is the sense of body position and movement, with conscious and unconscious components, that determines and conditions the human body's relationship with the environment. This quality of mechanosensitivity deteriorates in some pathologies and is responsible for some alterations of the locomotor system that appear in elderly persons. In those situations, the failure of proprioception reduces the quality of life of the subjects. The widespread use in developed countries of substitute joint prostheses makes it necessary to rethink the concepts of movement detection and perception. As such, this book examines the basics of proprioception as well as its function in the lower extremities, the head, in children with disabilities, and its connection with virtual reality.